ANALISIS YURIDIS KEKUATAN HUKUM AKTA PENGAKUAN UTANG YANG DIBUAT OLEH NOTARIS PADA SAAT TERJADI SENGKETA DI PENGADILAN (STUDI KASUS PUTUSAN MAHKAMAH AGUNG NO.2956.K/PDT/2013) - MELANI HANDAYANI (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Budiman Ginting2. Madiasa Ablizar3. Hasim Purba A loan agreement authentically made by a notary is followed by the issuance of a deed of acknowledgement of debt which is also made authentically by the notary. This is a normative legal research which is done to the Civil Code i.e. the Third Book of Agreement Law especially the loan agreement as referred to in Article 1721 of the Civil Code. This research is descriptive analytical endeavoring to describe, explain and analyze the research problems; and to find out the appropriate solution. The results of the discussion find out that the legal force of the deed of acknowledgement of debt made by the notary with an authentic deed is a perfect evidence for all parties when a dispute takes place at the court. Defendant I HH and Defendant II DH have been bound in a loan agreement that have been acknowledge by both through an authentic notarial deed i.e. the deed of acknowledgment of debt.Keywords: Deed of Acknowledgement of Debt, Notary, Dispute